2010
DOI: 10.1097/tp.0b013e3181e17014
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Simultaneous Liver/Kidney Transplants Are Equivalent to Kidney Transplant Alone: A Preliminary Report

Abstract: Background With adoption of Model for End-stage Liver Disease (MELD), the number of simultaneous liver-kidney transplants (SLK) has greatly increased. A recent registry study questioned the equity of allocating kidney transplants (KTx) simultaneously with liver transplantation due to poor outcomes (1). Methods To investigate outcome of KTx in SLK, all SLK (n=36) performed at our center from 1/2000–12/2007 were reviewed and KTx outcomes compared to those of kidney transplant alone (KTA) performed during that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 19 publications
3
43
2
1
Order By: Relevance
“…4 Several singleinstitution analyses also confirmed a decreased incidence of acute rejection in SLK patients. [8][9][10] Our study extends these previous studies in that the surveillance biopsies allowed us to examine subclinical rejection and lower levels of inflammation that do not meet criteria for acute rejection by Banff classification, but may affect graft outcome. 11 These data demonstrate that SCI is more common in KTA.…”
Section: Discussionmentioning
confidence: 71%
“…4 Several singleinstitution analyses also confirmed a decreased incidence of acute rejection in SLK patients. [8][9][10] Our study extends these previous studies in that the surveillance biopsies allowed us to examine subclinical rejection and lower levels of inflammation that do not meet criteria for acute rejection by Banff classification, but may affect graft outcome. 11 These data demonstrate that SCI is more common in KTA.…”
Section: Discussionmentioning
confidence: 71%
“…Most studies reported a detrimental effect of allosensitization on graft rejection: 9 studies reported a significant detrimental effect [13,14,39-45], and 7 studies reported a non-significant detrimental effect [12,15,16,46-49] (Figure 4). In contrast, 6 studies reported a non-detrimental effect of allosensitization on graft rejection [50-55].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, simultaneous transplant of syngeneic solid organ transplants may diminish the immunogenicity of one or both of the grafts. This has been suggested to contribute to improved kidney survival in simultaneous liver-kidney transplant, especially in recipients who are sensitized to donor HLA antigens prior to transplant [37].…”
Section: Clinical Immunosuppression Protocols For Solid Organ Transplantmentioning
confidence: 99%